2023
DOI: 10.1128/spectrum.00249-23
|View full text |Cite
|
Sign up to set email alerts
|

Effects of hydrogeochemistry on the microbial ecology of terrestrial hot springs

Carla Barbosa,
Javier Tamayo-Leiva,
Jaime Alcorta
et al.

Abstract: Temperature, pH, and hydrochemistry of terrestrial hot springs play a critical role in shaping thermal microbial communities. However, the interactions of biotic and abiotic factors at this terrestrial-aquatic interface are still not well understood on a global scale, and the question of how underground events influence microbial communities remains open. To answer this, 11 new samples obtained from the El Tatio geothermal field were analyzed by 16S rRNA amplicon sequencing (V4 region), along with 191 samples … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 117 publications
0
2
0
Order By: Relevance
“…Specifically, a massive 16S rRNA dataset analysis of 925 individual hot springs from the Taupo Volcanic Zone in New Zealand indicates that temperature only has a significant effect on diversity above 70°C, below which pH is the primary driver ( Power et al, 2018 ). Similarly, a recent global study of microbial diversity in hot springs from around the globe also indicated that pH, along with SO 4 2− concentration and abundances of certain phyla, is moderately correlated with microbial diversity, although most microbial variance remains unexplained ( Hamilton et al, 2019 ; Barbosa et al, 2023 ). A challenge when comparing results from multiple different studies, however, is that there are a lot of different biases in different studies, especially in analytical chemistry and nucleic acid extraction methods and amplification protocols in 16S rRNA sequencing ( Lauber et al, 2010 , 2013 ; Hinlo et al, 2017 ; Colman et al, 2021 ).…”
Section: Discussionmentioning
confidence: 89%
“…Specifically, a massive 16S rRNA dataset analysis of 925 individual hot springs from the Taupo Volcanic Zone in New Zealand indicates that temperature only has a significant effect on diversity above 70°C, below which pH is the primary driver ( Power et al, 2018 ). Similarly, a recent global study of microbial diversity in hot springs from around the globe also indicated that pH, along with SO 4 2− concentration and abundances of certain phyla, is moderately correlated with microbial diversity, although most microbial variance remains unexplained ( Hamilton et al, 2019 ; Barbosa et al, 2023 ). A challenge when comparing results from multiple different studies, however, is that there are a lot of different biases in different studies, especially in analytical chemistry and nucleic acid extraction methods and amplification protocols in 16S rRNA sequencing ( Lauber et al, 2010 , 2013 ; Hinlo et al, 2017 ; Colman et al, 2021 ).…”
Section: Discussionmentioning
confidence: 89%
“…(B) Ternary plot of the relative concentrations of major anions describing terrestrial hydrothermal systems water chemistry. Concentrations of SO₄ 2− , HCO₃ − , and Cl − were obtained from the published literature (Hose et al, 2000;Giaveno and María, 2010;Agusto, 2011;Agusto et al, 2012;Rosales Lagarde et al, 2014;Lin et al, 2015;Gaviria Reyes et al, 2016;Muñoz Lopez, 2017;D'Auria et al, 2018;Willis et al, 2019;Zhou et al, 2020b;Sriaporn et al, 2021;Sriaporn, 2022;Barbosa et al, 2023) and this study. Arisan et al 10.3389/fmicb.2024.1360268 Frontiers in Microbiology 10 frontiersin.org…”
Section: Pangenome Analysis Reveals Minimal Core Functions Of the Ign...mentioning
confidence: 97%